PHYSIOTHERAPY METHODS FOR PATIENTS WITH ADULT SCOLIOSIS - Evgeniya Dimitrova; Dimitar Nikolov (Scientific Publishing House. NSA Press, 2017)
Spinal deformities are a major demographic health issue among the adult population all over the world. Surgeons are often very conservative in the treatment of adult scoliosis because of the complication rates associated with the surgeries. A prerequisite to surgical interventions is usually failure of all appropriate conservative care. There is currently a lack of consensus on the most efficient conservative treatments for adult scoliosis. The aim of the present study is to investigate the effect of two different methods of exercise-based therapies on the treatment of adult idiopathic scoliosis. The research was done among 62 patients with scoliosis (10.93°Cobb) and back pain. They were randomly divided into two groups, depending on the physiotherapy (PT) protocol. To evaluate the effect of physiotherapy we used the posture assessment, visual analog scale (VAS) for pain, muscle strength test and Functional Rating Index (FRI). The control group - CG (n=37) performed a conventional physiotherapy program, including symmetrical exercises for the trunk muscles, lower and upper limbs, while the experimental group - EG (n=25) performed PT program, additionally including spinal mobilization, muscle energy technique, and postural therapy. The results after 6 months of treatment revealed a statistically significant improvement in the following parameters in the EG: the posture correction, pain index (according to VAS), muscle strength hand quality of live (p < 0.01). In the control group these results did not improve significantly. Conclusion: The combined use of spinal mobilization and postural therapy applied in the EG appears more effective than the conventional physiotherapy program used in the treatment of adult scoliosis.